Prototype for smart irrigation system based on solar cells - Saraheen, Hadeel; Al-hersh, Hammam (جامعة بوليتكنك فلسطين - طاقة, 2019)
The lack of electricity in remote agricultural areas and rising costs of diesel affect the high cost of pumping water to plants, so the use of solar energy is an effective alternative to pumping system. In this project, the smart irrigation system is designed, which provides remote control of the system and automatically irrigates plants, reducing the need for human intervention and can be controlled manually. This project aims at reducing waste of water, pumping the appropriate quantities of agricultural produce and relying entirely on the exploitation of solar energy. This system mainly depends on the photovoltaic units, the control unit and the remote control system based on Arduino. The system was reported in a practical way, the results were as expected and achieved the desired objectives.
CD , no of pages 53, طاقة 1/2019 , in the store
Keywords: smart irrigation system; solar cells